INFLUENCE OF EMPLOYEE TRAINING ON INNOVATION PERFORMANCE OF DTS IN KENYA. - Njine, Grace Wanjiru; Nzulwa, Dr. Joyce; Kamaara, Dr. Mary; Ombui, Dr. Kepha (Journal of Human Resource and Leadership, 2017)
Purpose: The purpose of the study was to examine the influence of employee training on Innovation Performance of DTS in Kenya. Methodology: This study adopted a descriptive survey design. The sampling frame of this study was derived from the database of the SASRA. Multistage sampling was used to select the sample of the study. The population of the study was the 181 DTS's operating in Kenya while the target population was 18 DTS's. The respondents were individual management staff. A questionnaire was used to gather primary data. Secondary data was collected through review of published literature such as journals articles, published theses and textbooks. Information was sorted, coded and input into the statistical package for social sciences (SPSS) version 21.0 for production of graphs, tables, descriptive statistics and inferential statistics. Results: The study found out that employee training and innovation performance are positively and significantly related (r=0.110, p=0.001), Unique Contribution to Theory, Practice and Policy: The study recommends for Deposit Taking Sacco's to come up with training programs which will better their understanding on their role in the SACCO. This will enable the trainee, upon completion, to perform efficiently. Keywords: Employee training, Innovation Performance, DTS.